Study of the strength of the blade of aircraft turbine - Yancachajlla Tito, Ubaldo (2006)
The work consists of demonstrating the possible utilization of the methods of the finite element for the case of calculating of a blade of turbine of a plane by method of the finite elements, first we find the critical stress in the blade due to the solicitations of the centrifugal force and the gas-dynamics, these generate stress of  traction and flexion principally. Comparing these results with the obtained one previously for traditional methods, managing to validate our results for the finite element method. Finally we will find the manners of vibration and natural frequencies of the blade of the turbine, coming to conclusions that they reconcile to the published ones in the literature. The method of the finite element represents a powerful tool that can be used satisfactorily for the optimization of the such complex designs as of the turbine.